Ownership Structure and Corporate Social Responsibility Disclosure in Bangladesh - Sufian, Mohammad Abu; Zahan, Muslima (International Journal of Economics and Financial Issues, 2013)
The quest of this research paper is to look into the association between corporate ownership structure variables and corporate social responsibility disclosure (CSRD). Seventy annual reports for the year 2010 of non financial companies with listed Dhaka Stock Exchange in Bangladesh have been considered as sample to find the empirical result of this study. The study reveals that the mean score of CSRD is 6.41 and 75 percent sample companies disclose seven items voluntarily which is 16 percent and 20 percent of total disclose-able items respectively. In general, companies have not responded enough to disclose CSR items in the annual reports. The multivariate analysis of this study shows that the ownership concentration of firm has a positive association with CSRD. But this study does not find any association of other variables of ownership structure such as number of shareholders, foreign ownership and board size on CSRD. It is expected that the contribution of this research work will be acknowledged by potential and present investors, stakeholders, policy makers, potential researchers and regulatory bodies of the country. Keywords: Corporate governance; ownership concentration; voluntary disclosure; outside ownership JEL Classifications: G32; G34; M14 <!--[endif] -->